HUBUNGAN PERSONAL HYGIENE DENGAN KEJADIAN HERVES DI SPN POLDA SUMUT HINAI - Masrah Masrah; Hilda Hilda (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
The skin is the organ that is located at the outermost and limits it from the human environment. The area of an adult's skin is about 1.5 m2 with a weight of approximately 15% body weight. Herves simplex is caused by Herves Simplex Virus (HSV). Vesicles arise in groups and cause pain. Herpes Simplex infection is characterized by repeated episodes of small blisters on the skin or mucous membranes, which are fluid and painful. The purpose of this study was to determine the relationship between personal hygine and the incidence of Herves in the North Sumatra Regional Police SPN. This type of research is analytic survey with a Cross Sectional approach. This research was conducted to students of the North Sumatra Police Department of Education in the North Sumatra Hinai National Police SPN with a population of 272 respondents and a sample of 74 respondents and the sampling technique was Simple random sampling. Data can be obtained by using questionnaires totaling 20 questions of personal hygiene and statements of herves' events. The data used are primary data, and tertiary data are analyzed using the chi-square test.The results of personal hygiene research with the incidence of herves showed that the results of the chi-square test obtained p-value <? in order to obtain the value of p = 0,012 or it is said that there is a relationship between personal hygiene and the event of herves. The conclusion of this study is that there is a positive and significant relationship between personal Hygiene incidence with p-value of 0,012 (p <0.05) in SPN North Sumatra Regional Police.